HUBUNGAN IKLIM KESELAMATAN DAN KEPEMIMPINAN KESELAMATAN DENGAN PARTISIPASI KESELAMATAN PADA PEKERJA PROYEK PEMBANGUNAN FASILITAS PERKERETAAPIAN DI MANGGARAI TAHUN 2022 - Siti Mursidati (2022)
Workers' participation in occupational safety and health has a 70% lower incidence of work accidents. The issue of safety participation is usually related to the impact of leadership and the safety climate. Leaders who emphasize the importance of K3 will improve the safety climate, resulting in increased employee participation in OHS. This study aims to analyze the relationship between safety climate and safety leadership with safety participation. The method used in this research is quantitative analysis using a cross-sectional study design. PT. X who worked in the railway facility construction project in Manggarai as many as 61 people who were taken using the total sampling method were the subjects in this study. Data was taken using the structured interview method using a questionnaire. The statistical test used is the Chi Square Test. The results of the analysis showed that there was a significant association between safety climate and safety participation (p-value=0.001 POR=8.10). Likewise, there was a significant association between safety leadership and safety participation (p-value = 0.000 POR = 16.28). So to increase safety participation, it is necessary to improve the safety climate and safety leadership through the company's commitment to worker safety.